Methyl Substituted Tin(IV) Derivatives of N-(o-Hydroxy Substituted Benzyl) Alanines - Nagarkoti, Sangita; Chandra, Madhup (Asian Journal of Chemistry, 2010)
Several methyl substituted tin(IV) derivatives of N-(o-hydroxy substituted benzyl) alanines have been prepared by the interaction of the corresponding methyl substituted tin isoproipoxide with the latter in various stoichiometries which were characterized by azeotrope and elemental analysis, as well as by spectral measurements.